2016
DOI: 10.1002/kin.20995
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Mechanistic Investigations on Some N,N‐Chelated Pt(II) Oxalate Complexes with Some “S” Containing Biorelevant Ligands at Physiological Condition

Abstract: The substitution of the chelating oxalate group by a group of nucleophiles, viz. thiourea (L1), 2‐thiouracil (L2), diethyldithiocarbamate (L3), dl‐penicillamine (L4), and thiosemicarbazide (L5) was studied under pseudo–first‐order conditions as a function of concentration and temperature using UV–vis spectrophotometry and stopped‐flow technique. π‐Accepting effects are often used to account for the unusual high lability of Pt(bipy) complexes. The complexes [Pt(dach)(oxalate)] (1) (dach = cis‐1,2‐diaminocyclohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Evaluation of the rate constant k 1 . The rate constant of the first step (I → II in Scheme ) is dependent on the thione concentration, which is consistent with previous reports . At constant temperature, the rate constant ( k obsd1 ) for reaction of Tu or DIAZ with [Au( cis ‐DACH)Cl 2 ]Cl and [Au( cis ‐DACH) 2 ]Cl 3 was obtained from the slopes of the plots of ln Δ versus time ( t ) (Eq.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Evaluation of the rate constant k 1 . The rate constant of the first step (I → II in Scheme ) is dependent on the thione concentration, which is consistent with previous reports . At constant temperature, the rate constant ( k obsd1 ) for reaction of Tu or DIAZ with [Au( cis ‐DACH)Cl 2 ]Cl and [Au( cis ‐DACH) 2 ]Cl 3 was obtained from the slopes of the plots of ln Δ versus time ( t ) (Eq.…”
Section: Resultssupporting
confidence: 88%
“…The kinetics of the formation and equilibrium hydrolysis of [AuBr 4 ] − and [AuCl 4 ] − revealed a two‐term rate law and indicated that their hydrolysis was faster than the analogous Pt(II) complexes . Ray et al evaluated the activation parameters of kinetics for the substitution reactions of cis ‐[Pt(DACH)(H 2 O) 2 ] 2+ , DACH = cis ‐1,2‐diaminocyclohexane, with dipeptides containing glycine, glutathione, and penicillamine under pseudo–first‐order conditions depending on pH, ligand concentration, and complex formation .…”
Section: Introductionmentioning
confidence: 99%
“…The recorded absorption at 681 cm −1 was also attributed to the Pt–N bond vibration (Figure 7). [ 87 ]…”
Section: Resultsmentioning
confidence: 99%
“…The recorded absorption at 681 cm −1 was also attributed to the Pt-N bond vibration (Figure 7). [87] F I G U R E 4 Elemental composition of the final product of (A) ZnO NPs@polymer shell compared to (B) ZnO NPs@polymer shell.…”
Section: Fesemmentioning
confidence: 99%
“…The remaining sites are occupied by two monodentates or a bidentate ligand. Examples are Pt(II) complexes, which have N,N‐ or N,S‐ bidentate nonleaving ligands and these usually display a two‐step consecutive substitution of the labile leaving groups, with rates that are dependent on the electronic (σ‐donor/π‐acceptor) and steric demands of the resident ligand as well as the nucleophilicity of the labile ligands. Even in complexes where the coordinated bidentate ligand is symmetrical, substitution occurred consecutively .…”
Section: Introductionmentioning
confidence: 99%